Symptomatic Anterior Cerebral Artery Vasospasm after Brainstem Hemangioblastoma Resection: A Case Report. Issue 2 (April 2014) - Prontera, Andrea; Puzzolante, Annette; Carpeggiani, Paolo; Pavesi, Giacomo
Diffuse cerebral vasospasm is a rare complication after brain tumour resection as opposed to that following an aneurysmal subarachnoid haemorrhage. Sellar tumours are among the most common pathologies and locations associated with this complication. Removal of posterior cranial fossa lesions is uncommonly associated with vasospasm, with only nine reported cases. We describe a case of diffuse symptomatic vasospasm mainly involving the right anterior cerebral artery, angiographically confirmed, after resection of a haemangioblastoma of the medulla in an adult patient with von Hippel-Lindau disease. The possible pathogenesis of this phenomenon is discussed.